Pemodelan proses kerja turnaround pabrik menggunakan Business Process Model Notation (BPMN) - Rochmatullah, Faris Yasin; Waluyo, Minto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to model the work process of factory turnaround using Business Process Model Notation (BPMN) at PT XYZ, which is the largest producer of urea fertilizer in Southeast Asia. Turnaround maintenance is a repair activity carried out when the factory is in a state of shutdown, with the aim of restoring factory performance in accordance with the desired design capacity. Through BPMN modeling, this study identifies critical stages in the process of planning, prepare, implementing, and evaluating turnarounds, as well as potential risks that can affect the smooth running of production. The results of the analysis show that this modeling not only improves the understanding of the workflow, but also helps in more effective decision-making. Thus, the implementation of BPMN at PT XYZ is expected to improve operational efficiency and reduce production disruptions, which in turn has a positive impact on the availability of fertilizers for farmers. This research has made a significant contribution to the development of planned maintenance methodologies in the manufacturing industry.